2011
DOI: 10.2460/ajvr.72.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Fetal protection in heifers vaccinated with a modified-live virus vaccine containing bovine viral diarrhea virus subtypes 1a and 2a and exposed during gestation to cattle persistently infected with bovine viral diarrhea virus subtype 1b

Abstract: 1 dose of a BVDV1a and 2a MLV vaccine administered SC or IM prior to breeding helped protect against fetal infection in pregnant heifers exposed to cattle PI with BVDV1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…When calves with neutralizing titers to BVDV-1b and below were exposed to PI calves with BVDV-1b, some, but not all became viremic [52]. A study using BVDV-1b PI calves as the challenge model indicated that pregnant vaccinated heifers (BVDV-1a and BVDV-2a immunogens) with serum titers of 128 to BVDV-1b and above were protected against fetal infections [57]. Eight control heifers and two vaccinated heifers with titers <4 had infected fetuses, and the other two control heifers control heifers aborted before the collection date.…”
Section: Immunity To Bvdv In Acute Infections and Response To Vaccinamentioning
confidence: 99%
“…When calves with neutralizing titers to BVDV-1b and below were exposed to PI calves with BVDV-1b, some, but not all became viremic [52]. A study using BVDV-1b PI calves as the challenge model indicated that pregnant vaccinated heifers (BVDV-1a and BVDV-2a immunogens) with serum titers of 128 to BVDV-1b and above were protected against fetal infections [57]. Eight control heifers and two vaccinated heifers with titers <4 had infected fetuses, and the other two control heifers control heifers aborted before the collection date.…”
Section: Immunity To Bvdv In Acute Infections and Response To Vaccinamentioning
confidence: 99%
“…Experimental design-Heifers were allocated to a vaccinated (n = 22) or unvaccinated control (11) group in accordance with a generalized randomized block study design with weight used as the blocking factor. The start of the study was designated as day 0.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies [4][5][6]11 that have been conducted to assess fetal protection against BVDV infection provided by vaccination of dams prior to BVDV exposure have involved only an instantaneous exposure to a challenge strain. Results of studies 4,5 conducted to evaluate BVDV vaccine efficacy in which a single intranasal dose of BVDV was used as the challenge exposure indicated that 95% to 100% of the fetuses from vaccinated dams were protected against PI.…”
Section: Ruminants/ Camelidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[259][260][261][262][263] Lesser degrees of protection were observed in other studies when vaccinated pregnant cattle were exposed to PI cattle, which is considered a more rigorous and realistic challenge model. [264][265][266][267] While prolonged and complete protection from development of PI calves was demonstrated in a study using PI cattle as the challenge model, 264 under field conditions, success of vaccination to prevent fetal infection depends on various factors including timing of vaccination, nutritional and immune status of animals, cross-protection of vaccine and field strains, and number of vaccinations administered before breeding.…”
Section: Vaccinationmentioning
confidence: 99%